Development of animal feed from waste to wealth using Napier Grass and Palm Acid Oil (PAO) from Palm Oil Mill Effluent (POME) - Farah Amalina, Ishak; Muhammad Haziq, Jamil; Abdul Syukor, Abd Razak; Nurul Huwaida, Abd Razak; Anuar, Zamani; Mohd Rashid, Ab Hamid (2018)
This study is to investigate the effectiveness of feeding cattle with a mixture of palm acid oil (PAO) from palm oil mill effluent (POME), water lettuce, coconut waste and Napier grass. These materials will be mixed and form a feed formulation. This study also wants to develop a cattle feed that will help to reduce the water lettuce and coconut waste negative impact to the environment. Besides that, the best formulation of the cattle feed will be determined. The amount of each material will be different for each formula. This cattle feed will use the waste to follow the Green Technology. The formulation of the feed is based from Department of Veterinary Services Feeding Guide book. This study is focus on reducing the negative impact to the environment by utilizing the waste of POME, coconut waste and water lettuce. There are three formulation that was tested on cattle to determine the most suitable formulation. The formulation has different amount of each material. The nutrient in each formulation was calculated based on feeding guides by Department of Veterinary entitled nutrient composition of Malaysian feed materials and guides to feeding of cattle and goats. There are four cattle that was involved in this study. Three cattle were fed with the formulation. Meanwhile, the other one was fed with its regular feeds which is Napier Grass only and act as the control. The result obtained will be compared with the control cattle. The feed intake of each cattle was recorded. The result shows that the formulation is good for high growth performance of the cattle compare to the regular feeds. This is because the formulation has more nutrients in it. In fact, it has more nutrient than the cattle need to grow. The control cattle did not gain as much as formulation A. Thus, this prove that the formulation is effective compare to the regular feeds and it is cheaper. Apart from that, the high growth performance can help to cater the high demand of meats consumption.